Microdontia treatment with orthodontics and indirect restoration: clinical case - Gontijo, Sávio Morato de Lacerda; Gonçalves, Laura Costa; Arantes, Fernanda Novais; Silami, Francisca Daniele Jardilino; Novaes Júnior, João Batista; Barreiros, Ivan Doche (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Objective: This case report aims to present the microdontia treatment of tooth 35 through pre-prosthetic orthodontics, followed by re-anatomization with an indirect restoration. Case report: A 21-year-old female patient presented with microdontia in tooth 35, with a distalized and vestibularized crown. In addition, tooth 34 was gyroverted with mesial diastema. Orthodontic mechanics with segmented arch were used to centralize tooth 35 in the alveolar ridge, close the diastema in the mesial of tooth 34, and correct its gyroversion. For lingualization of tooth 35, a first-order fold (in set) was performed, and for mesialization, an open-coil spring was used between teeth 35 and 36. A closed-coil spring was used to delimit the movement of tooth 35 to mesial. The force applied by the open spring for mesialization of tooth 35 was transmitted to tooth 34, through the closed spring, resulting in its mesialization; this, closed the diastema between teeth 33 and 34 and corrected the gyroversion. Subsequently, the coronary preparation was performed with diamond tips 1014 and 3146, and confection of the temporary crown in acrylic resin. For the ceramic system, IPS™ e.max Press was used. The ceramic crown was luting using the adhesive technique, followed by light curing for 40 seconds on each face of the tooth. Conclusion: It can be concluded that the re-anatomization of a small tooth should be the first treatment option. However, pre-prosthetic orthodontic treatment may be necessary.